Postales de Río - Doria, Martín (Colección Tinta roja., 2013)
Luna is a doctor under the watch of health guards in a public hospital in the Buenos Aires suburbs. His mental state is always on the verge of collapse due to stress, a misguided divorce, an elusive teenage daughter, arm tightening in the hospital, and a gloomy and threatening social context. This becomes the breeding ground that, together an irresistible trigger-- the appearance of a young cumbia singer who awakens all his sexual fantasies-- will lead him in free fall into the world of drugs, the war between drug dealers, mysticism and rapt love.